-3x+3=-2x+1

Simple and best practice solution for -3x+3=-2x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+3=-2x+1 equation:


-3x+3=-2x+1

We simplify the equation to the form, which is simple to understand
-3x+3=-2x+1

We move all terms containing x to the left and all other terms to the right.
-3x+2x=+1-3

We simplify left and right side of the equation.
-1x=-2

We divide both sides of the equation by -1 to get x.
x=2

See similar equations:

| 4(3-2x)+2=2 | | (5b)*(-9x)= | | 2*cosx*sinx-cosx=1 | | 7(2+5h)=-17 | | C+9=18 | | 7(2+5h)=-71 | | 6+1.25a=1.1a | | (x^2+12x+40)/(x+7) | | 13/5=n | | .02-.05x+.3x=-.68 | | 16-4j+12j-19=-3j+2-7j+4 | | -12y+8=-11y+9 | | 3.2x=4x+16 | | x^2+1x-72=0 | | -x^2-15x-50=0 | | 2w^4= | | 7U^5+10U^3/-U^2 | | 33/n=3 | | 10-3(2x+5y)= | | 12-5x=x+5 | | -3/8h=9 | | sqrt(14x-6)=x+3 | | y^2-10y-8x-9=0 | | 6c+2-5c=-24+8 | | 9y+12x=294 | | -1/4(12x-20y) | | 6x10^4/3x10^2 | | x+1x-30=Y | | A^2-15a-54=0 | | A^3b^-5/A^-5b^3 | | 10.00+.10m=.35m | | 2n^2+2n-7=0 |

Equations solver categories